2023
DOI: 10.1111/1750-3841.16890
|View full text |Cite
|
Sign up to set email alerts
|

Drying kinetics prediction and quality effect of ultrasonic synergy vacuum far‐infrared drying of Codonopsis pilosula

Tongxun Wang,
Xinyu Ying,
Qian Zhang
et al.

Abstract: By using ultrasonic synergy vacuum far‐infrared drying (US‐VFID), the effects of different conditions on the drying kinetics, functional properties, and microstructure of Codonopsis pilosula slices were studied. The sparrow search algorithm (SSA) was used to optimize the back‐propagation (BP) neural network to predict the moisture ratio during drying. With the increase of ultrasonic frequency, power and radiation temperature, the drying time of C. pilosula was shortened. The drying time of US‐VFID was 25% shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…The fitness curve illustrates the efficiency and capability of the NGO-BP neural network, as depicted in Figure 4b, showcasing rapid convergence and high accuracy after approximately 40 evolutions. The mean absolute error (MAE) was utilized as a criterion for evaluating the prediction results of the model [25], and the optimized MAE prediction values of the BP neural network and NGO-BP neural network were 0.01393 and 0.01346, which indicated that the NGO-BP neural network model could obtain a better prediction of the water ratio. The predicted and experimental values for the test dataset are shown in Figure 4c, where the experimental values and the moisture ratios predicted by NGO-BP are in good agreement and the model is well fitted.…”
Section: Moisture Content Prediction Based On Ngo-bp Modelmentioning
confidence: 99%
“…The fitness curve illustrates the efficiency and capability of the NGO-BP neural network, as depicted in Figure 4b, showcasing rapid convergence and high accuracy after approximately 40 evolutions. The mean absolute error (MAE) was utilized as a criterion for evaluating the prediction results of the model [25], and the optimized MAE prediction values of the BP neural network and NGO-BP neural network were 0.01393 and 0.01346, which indicated that the NGO-BP neural network model could obtain a better prediction of the water ratio. The predicted and experimental values for the test dataset are shown in Figure 4c, where the experimental values and the moisture ratios predicted by NGO-BP are in good agreement and the model is well fitted.…”
Section: Moisture Content Prediction Based On Ngo-bp Modelmentioning
confidence: 99%